Vascular endothelial growth factor control mechanisms in skeletal growth and repair. Issue 4 (29th December 2016) - Hu, Kai; Olsen, Bjorn R.
Abstract : Vascular endothelial growth factor A (VEGF) is a critical regulator of vascular development and postnatal angiogenesis and homeostasis, and it is essential for bone development and repair. Blood vessels serve both as structural templates for bone formation and they provide essential cells, growth factors and minerals needed for synthesis and mineralization, as well as turnover, of the extracellular matrix in bone. Through its regulation of angiogenesis, VEGF contributes to coupling of osteogenesis to angiogenesis, and it directly controls the differentiation and function of osteoblasts and osteoclasts. In this review, we summarize the properties of VEGF and its receptors that are relevant to bone formation and repair; the roles of VEGF during development of endochondral and membranous bones; and the contributions of VEGF to bone healing during different phases of bone repair. Finally, we discuss contributions of altered VEGF function in inherited disorders with bone defects as part of their phenotypes, and we speculate on what will be required before therapeutic strategies based on VEGF modulation can be developed for clinical use to treat patients with bone growth disorders and/or compromised bone repair. Developmental Dynamics 246:227–234, 2017 . © 2016 Wiley Periodicals, Inc. Key Findings: Coupling of osteogenesis to angiogenesis by VEGF. VEGF controls osteoblast and osteoclast differentiation and function. VEGF contributes to several stages of bone repair. Altered VEGF function in inherited bone disorders. Therapeutic strategies based on VEGF modulation.